Looking into the abyss? Brazil at the mid-2010s - Fernando J. Cardim de Carvalho (Levy Economics Institute of Bard College, 2016)
The Brazilian economy in 2015 was afflicted by a lethal combination of decelerating activity and accelerating inflation. Expectations for 2016 are equally or even more adverse, since the effects of rising unemployment emerge only after a lag. The domestic debate has pitted analysts who believe the crisis is due exclusively to past policy mistakes against those who believe that all was well until the government decided to implement austerity policies in 2015. A closer examination of the evidence shows that, in fact, both causes contributed to the crisis. But it also suggests that its depth has a more proximate cause in the political collapse of the federal government in 2015, which led Brazilian society to an impasse for which one cannot yet visualize the solution.
Keywords: E31; E32; E60; 330; Brazilian Economy; Macroeconomic Policy; Great Recession